Trends in household portfolio composition - Jesse Bricker; Kevin Moore; Jeffrey P. Thompson (Federal Reserve Bank of Boston, 2019)
We use data from the Federal Reserve Board's Survey of Consumer Finances (SCF) to explore how household asset portfolios in the United States evolved between 1989 and 2016. Throughout this period, two key assets - housing and financial market assets - drove the household balance sheet evolution; however, we find a great heterogeneity in the balance sheets that averages and aggregates conceal. We observe that ownership of assets has become more concentrated over time, and we show that nearly all of the time series variation in financial vulnerabilities in family balance sheets is due to middle-income families, who hold most of their assets in housing and are often the most highly leveraged income group in the housing market. Tracking the evolution of wealth over time among birth-year cohorts, we observe the standard life-cycle asset accumulation processes among low-, middle-, and high-income families.
Keywords: D31; G11; D14; E21; E22; G51; 330; portfolio composition; asset inequality; life-cycle savings patterns; financial risk